PENAKSIR PRODUK YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN KOEFISIEN VARIASI DAN KOEFISIEN KURTOSIS - Isnaini '; Arisman Adnan; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article reviews three product estimators for the population mean in simple random sampling. They use the coefficient of variation and coefficient of kurtosis of auxiliary variables. This article is the reviewof Singh’s article [Jour. Ind. Soc. Ag. Statistics 56(3): 267-275]. Those three estimators are biased. Then their Mean Square Error(MSE) are determined. Furthermore, MSE of each estimator is compared to obtain the most efficient estimator. This study shows that the modification of the product estimator is the most efficient estimator if the conditions are met.